Cyclostratigraphy and high-frequency sedimentary cycle framework for the Late Paleozoic Fengcheng Formation, Junggar Basin - Liu, Guoyong; Zhang, Rui; He, Xiangwu; Wei, Ren; Zhu, Rukai; Tang, Yong; He, Wenjun; Zheng, Menglin; Chang, Qiusheng; Wang, Ran; Zhao, Xinmei (Frontiers in Earth Science, 2023)
The Late Paleozoic Fengcheng Formation within the Mahu Sag of the Junggar Basin (China) harbors the world's oldest alkaline lake hydrocarbon source rocks. Spectral analysis of the natural gamma-ray (GR) series obtained from four boreholes traversing the Fengcheng Formation, with wavelength ranges of 28.4–50, 5.9–12.6, 2.3–3.9, and 1.2–2.7 m. These were controlled by Early Permian astronomical cycles, including 405 kyr long eccentricity, 100 kyr short eccentricity, 34.2 kyr obliquity, and 20.7–17.4 kyr precession. The most significant cycle was notably that of the 405 kyr long eccentricity, which was instrumental for dividing and correlating the high-frequency sedimentary sequences in lacustrine shales. Nine intermediate-term and 36 short-term base-level cycles were identified in the P1f1 and P1f2 members of the Fengcheng Formation. These cycle types are equal to the 405 kyr long eccentricity cycle and ~100 kyr short eccentricity cycle, respectively. The paleolake-level variations in the Fengcheng Formation were reconstructed using sedimentary noise modeling, revealing that lake levels reached their highest value during the deposition of the P1f2 Member. The spatial distribution patterns of lithofacies in the Fengcheng Formation can be clearly demonstrated within the isochronous cycle framework under the constraints of long eccentricity cycles. The use of astronomical cycles in isochronous stratigraphic correlation offers great potential for characterizing alkaline lacustrine sequences and predicting favorable areas for shale oil exploration with higher accuracy.